2016
DOI: 10.1016/j.jss.2016.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide secondary overtriage in level 3 and level 4 trauma centers: are these transfers necessary?

Abstract: Background Secondary overtriage (SO) refers to the interfacility transfer of trauma patients who are rapidly discharged home without surgical intervention by the receiving institution. SO imposes a financial hardship on patients and strains trauma center resources. Most studies on SO have been conducted from the perspective of the receiving hospital, which is usually a level 1 trauma center. Having previously studied SO from the referring rural hospital’s perspective, we sought to identify variables contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Our high rate of PATs may have followed from our 8,9,26,41 hours; and nonreceipt of an "operation," 8,9,15,20,26,31,41,43 which can denote an operating room-level intervention, 43 any additional medical or surgical intervention, 17 or select procedures. 28 Additional criteria, such as no critical care admission 20 or advanced imaging studies, 15 have also been requirements of a PAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our high rate of PATs may have followed from our 8,9,26,41 hours; and nonreceipt of an "operation," 8,9,15,20,26,31,41,43 which can denote an operating room-level intervention, 43 any additional medical or surgical intervention, 17 or select procedures. 28 Additional criteria, such as no critical care admission 20 or advanced imaging studies, 15 have also been requirements of a PAT.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of the referring hospital, it has been shown that head CT prior to pediatric transfer reduces the odds of unnecessary transfer (OR 0.33), 24 an observation consistent with studies involving adult populations (OR 0.30-0.49). 9,26 We limited our study population to individuals with imaging because we suspected the primary predictor of an avoidable transfer would be pretransfer CT results, and interpreting the need for transfer in light of the outside hospital CT results would best reflect clinical practice. In point of fact, we observed that 86% of both patients with isolated, nondisplaced skull fractures and patients who did not undergo imaging were discharged within 1 hospital day in contrast to 54% of patients whose imaging denoted significant cranial pathology.…”
Section: Discussionmentioning
confidence: 99%
“… 1 – 3 There are several scoring systems to triage trauma patients and permit efficient allocation of medical resources to the most severely injured individuals. 4 , 5 Clinical investigators have made great efforts to improve medical outcomes in severely injured patients. The key to successful treatment of such patients is prompt initiation of necessary tests and procedures; 6 8 delayed initiation of these can be fatal in certain circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma patients who were admitted to the hospital and were hospitalized for more than 48 hours, or received operative management, or whose injury resulted into death were considered accurately triaged. Patients with length of stay ≤48 hours who did not receive operative management and were discharged alive were considered not accurately triaged, as they could have been successfully treated at lower level of healthcare facilities 13–17. To determine whether the observed overtriage and undertriage could be reduced by setting certain prehospital criteria for the transfer of trauma patients, the US trauma transfer’s (EMS) field triage algorithm was applied to all of our trauma patients 18…”
Section: Methodsmentioning
confidence: 99%